Co-Teaching: a successful factor on teacher training through collaborative practices and professional advice. - Cortez Soto, Ana Berenice; Serrato Salazar, Dan Isaí (2018)
The emphasis of the present study was to design a didactic proposal to help pre-service teachers to develop their teaching skills through collaboration and guidance from expert teachers on the field of linguistics and education. This study is based on the co-teaching model that is defined as the joint work of two teachers with the same group of students sharing planning, organization, delivery as well as physical space (Bacharach, Heck & Dahlberg, 2010). Co-teaching promotes coaching and training for pre-service teachers to apply theory into practice during the different steps of teaching: co-planning, co-delivering, and co-evaluation (Conderman & Hedin, 2012). This research looked for the perceptions that pre-service teachers had about the teaching practicum as well as the roles that cooperating teachers took regarding the supervision of pre-service teachers. According to the findings pre-service teachers realized they did not collaborate with cooperating teachers during planning, delivery and evaluation of the lessons. On the other hand, cooperating teachers were aware of the need of establishing collaborative teaching roles through a formal regulation that fosters commitment between participants. The didactic proposal aims to establish a link of collaboration between pre-service teachers and cooperating teachers through a teaching practice protocol based on the co-teaching model. Pre-service teachers seek for benefits that derived from the exercise of teaching like development of teaching skills, improvement in language, development of social skills related to classrooms and acquisition of work experience. This emerging practice of co-teaching in teacher training holds great promise in transforming the process of teacher preparation and in meeting the needs of teachers from the XXI century (Suárez, 2016).